1998
DOI: 10.1007/s001250050885
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of glycaemic level to advanced glycation end-product (AGE) accumulation and retinal pathology in the spontaneous diabetic hamster

Abstract: The most characteristic findings of diabetic background retinopathy in humans are increased capillary permeability and progressive vascular occlusions. According to studies correlating angiographic in vivo findings with post-mortem retinal digests microaneurysms cluster around areas of capillary non-perfusion [1,2], possibly in an early abortive attempt at retinal new vessel formation. From earlier work it is known that pericytes may disappear leaving behind empty pockets in the capillary basement membrane [3]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…The exact mechanism is still unclear, but the activation of protein kinase C and the activity of NAD(P)H oxidase are thought to be key events by which advanced glycation end products may trigger higher ROS production [41]. Similar results were obtained for human umbilical vein endothelial cells incubated with N (carboxymethyl) lysine -ovalbumin [15].…”
supporting
confidence: 58%
“…The exact mechanism is still unclear, but the activation of protein kinase C and the activity of NAD(P)H oxidase are thought to be key events by which advanced glycation end products may trigger higher ROS production [41]. Similar results were obtained for human umbilical vein endothelial cells incubated with N (carboxymethyl) lysine -ovalbumin [15].…”
supporting
confidence: 58%
“…It can nevertheless be assumed that regular physical activity, as an integrated part of an active lifestyle, may influence the accumulation of AGEs in the organism because the amount of these compounds is conditioned by glycaemia levels [58]. Therefore, the improvements of glycaemic control in DM2 due to physical exercise, usually linked with the reduction of the peripheral resistance to insulin [37, 72,132], could attenuate the formation and accumulation of AGEs in the tissue.…”
Section: Ages and Regular Physical Activitymentioning
confidence: 99%
“…Previous studies in long-term diabetic rodents have demonstrated AGE accumulation in vascular BMs of retinal capillaries [15,37,38,39]. This AGE accumulation may play a significant role in progression of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 89%